PENGARUH LITERASI KEUANGAN, LITERASI DIGITAL, PROMOSI DAN USIA TERHADAP PENGUNAAN PINJAMAN ONLINE - Aldifayan, Nisrina; Setiawan, Amelia; Djajadikerta, Hamfri (An Nuqud Journal of Islamic Economics, 2025)
This study is a study that uses a quantitative approach using a causal research method that is carried out by distributing questionnaires to auditors. The questionnaires were successfully collected from 98 respondents from the Fintech facility user community. The data was processed using the IBM SPSS Statistics version 29 program. Data processing was carried out using multiple regression analysis. The data was also tested for quality (Validity Test and Reliability Test), multiple regression variable analysis, classical assumption test, and hypothesis test (partial test and simultaneous test). The results of this study indicate that financial literacy and digital literacy do not have a significant effect on the use of paylater services. On the contrary, promotions have been shown to have a significant influence in encouraging increased use of paylater. The age factor also does not show a significant effect on the use of this service. However, overall, this study reveals that financial literacy, digital literacy, promotions, and age together have a significant effect on the use of paylater, with most of the variation in the use of this service being explained by a combination of the four variables